2015
DOI: 10.1055/s-0040-1703885
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Structured Teaching Programme on Prevention of Icu Delirium Among Nurses

Abstract: Delirium is extremely common in intensive care unit (ICU) patient due to comorbidity, critical illness and iatroogenesis. This complication of hospital stay is extremely hazardous in older persons and is associated with prolonged hospital stays. yet ICU nurses and physicians are usually unaware of the presence of hypoactive delirium and only recognize this disturbance in agitated patients (hyperactive delirium).The aim of the study was to assess the existing knowledge of ICU staff nurses regarding ICU delirium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Accumulating evidences demonstrate that educational intervention could enhance nurses' knowledge and skills and enable them to identify ICU delirium early (Christensen, 2014;Prabhu, Shetty, Prabhu, Pais, & Kuriakose, 2015;Siddiqi, 2011;van de Steeg, Ijkema, Wagner, & Langelaan, 2015;Varghese, Macaden, Premkumar, Mathews, &Kumar, 2014). Mc Donnell andTimmins (2012) assessed the relationship between training for delirium received and the level of difficulty experienced when dealing with delirious behaviour; they found that nurses who received education were less likely to have difficulties in managing patients with delirium.…”
Section: Ramoo Et Almentioning
confidence: 99%
“…Accumulating evidences demonstrate that educational intervention could enhance nurses' knowledge and skills and enable them to identify ICU delirium early (Christensen, 2014;Prabhu, Shetty, Prabhu, Pais, & Kuriakose, 2015;Siddiqi, 2011;van de Steeg, Ijkema, Wagner, & Langelaan, 2015;Varghese, Macaden, Premkumar, Mathews, &Kumar, 2014). Mc Donnell andTimmins (2012) assessed the relationship between training for delirium received and the level of difficulty experienced when dealing with delirious behaviour; they found that nurses who received education were less likely to have difficulties in managing patients with delirium.…”
Section: Ramoo Et Almentioning
confidence: 99%